South Carolina in the Civil War and Reconstruction eras : essays from the proceedings of the South Carolina Historical Association - Bonner, Michael Brem, 1970-; Hamer, Fritz (The University of South Carolina Press, 2016)
A collection of important, but little-known, scholarship examining the Civil War and Reconstruction.